IMPLEMENTASI PSAK 46 TENTANG PAJAK PENGHASILAN DALAM PENYUSUNAN LAPORAN KEUANGAN PT. INDOFOOD SUKSES MAKMUR TBK - Adhwa Naifah Kamilla; Kayla Ramadhani Putri Jodiansyah; Luciano Deandra; Shafina Marita Fatisya (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Taxes are a crucial element in the preparation of financial statements because they are a major liability that must be recorded in accordance with applicable accounting standards, particularly PSAK 46 on Income Tax. PSAK 46 regulates the procedures for recording and presenting current and deferred taxes so that financial statements can present tax information transparently and accurately. This study examines the application of PSAK 46 at PT Indofood Sukces Makmur Tbk using data from the 2024 interim consolidated financial statements. The findings show that PT Indofood consistently implements PSAK 46 in recognizing current taxes, deferred taxes, and prepaid taxes. The company's financial statement disclosures show a temporary difference between fiscal profit and accounting profit in accordance with the standard. In addition, the implementation of PSAK 46 at PT Indofood shows a better level of depth and comprehensiveness compared to previous studies on similar companies. The implementation of this standard not only promotes compliance but also strengthens the transparency and credibility of financial statements, as well as assisting companies in tax planning and managing long-term fiscal risks. Thus, PSAK 46 plays an important role in ensuring reliable and credible financial statements for various stakeholders.